Perancangan Perbaikan Proses Produksi Komponen Bodi Mobil Daihatsu dengan Lean Manufacturing di PT. “XYZ” - Satria Khalif Isnain; Putu Dana Karningsih (Jurnal Studi Manajemen dan Bisnis, 2018)
Astra Daihatsu Motor Company. Potential market for automotive is continuously growing which is positive signal for automotive businesses. However nowadays competition is also getting stronger. Therefore PT Inti Pantja Press Industri should efficiently manage their production. One way is by reducing and eliminating waste in its production. Production process in PT. Inti Pantja Press Industri is still having several problems. Based on early observation there are bottleneck in subassy processes and also defective product. Reffering to these problems, it can be indicated that there are several waste in production process of PT. Inti Pantja Press Industri.Therefore, Lean Manufacturing  approach  is  utilized  to  reduce  or  eliminate  waste  in  production processes. First,   various waste are identified using Value Stream Mapping. Borda Count Method is used for determining critical waste that occur, they are as follow: waste waiting, defect, and overproduction that cause over inventory finish product. Then, 5 Whys Analysis specifies root causes of waste waiting and waste defect. By using Failure Mode and Effect Analysis, highest priority of root causescan be selected, which are  operator  do  not  clean  dies  before  press  process,  operator  do  not  replace components that has already over its lifetime (wear) and rust on finish product part. Recommendations for improvements are conducted by implementating Poka Yoke method,  they  are:  installation  of  sensors  and  equipment  in  Press  machines  and wrapping finish part product.